Acoustic Quality of a Tensile Membrane Structure Used as a Lecture Hall, and Proposals for its Improvement. Issue 4 (December 2014) - Nocera, Francesco; Gagliano, Antonio; Evola, Gianpiero; Gioia, Mirko Cascio
Tensile membrane structures can offer considerable weight saving, becoming attractive for designers in several technological areas. They also have the advantage of realizing an enormous space without columns and beams. Furthermore, they can produce a unique atmosphere as well as savings on electricity for interior lighting, due to their light transmission properties. Unfortunately, membrane structures have serious defects in sound-insulation performance, rain-noise problems and low thermal insulation. Consequently, it is not easy to ensure acoustic comfort inside tensile membrane structures, because the techniques that normally apply to traditional buildings are not suitable in lightweight structures. For these reasons, this paper investigates the acoustic behaviour of a tensile membrane structure used as a lecture room, through instrumental techniques and simulation with software for room acoustics, in order to propose possible solutions applicable to similar structures.